Supraorbital Nerve Radiofrequency for Severe Neuralgia Caused by Herpes Zoster Ophthalmicus - Huan Zhang; Huadong Ni; Songlei Liu; Keyue Xie (Pain Research and Management)
Background. Radiofrequency of the Gasserian ganglion can be used for ophthalmic herpetic neuralgia (OHN), but it is associated with complications. This study aimed to use the supraorbital nerve for computed tomography- (CT-) guided radiofrequency thermocoagulation to treat refractory OHN. Methods. This was a retrospective case series study of patients with simple or combined OHN treated at our hospital between 06/2012 and 06/2018. The numerical rating score (NRS), spontaneous pain, allodynia, gabapentin dosage, paracetamol/oxycodone dosage, patient global impression of change (PGIC) score, Barrow numbness score, postoperative 360-day recurrence rate, and complications were recorded before the operation and at 1, 30, 90, 180, and 360 days after the operation. Results. Compared with baseline, the NRS was decreased, and PGIC was increased at postoperative 1, 30, 90, 180, and 360 days, and the gabapentin and paracetamol oxycodone doses at postoperative 30, 90, 180, and 360 days were decreased (all P<0.001). Compared with 1 day after the operation, numbness was decreased at 30, 90, 180, and 360 days after the operation (P<0.001). Compared with baseline, the number of patients with allodynia at each time point after the operation was decreased (P<0.001), but without a difference for spontaneous pain (P=0.407). No subjects showed drooping eyelid, corneal ulcers, eyeball damage, decreased vision, and other severe complications. Conclusion. CT-guided supraorbital nerve radiofrequency thermocoagulation for the treatment of OHN can effectively relieve pain and reduce the dose of analgesics, without any serious complication. This study suggests that this technique is feasible and applicable to clinical practice.